(untitled) (Journal of Asian Development Studies, 2025)
This study investigates the population census and socioeconomic impacts of Salix species in Gilgit Baltistan, Pakistan. Comprehensive field surveys and structured interviews were carried out in Danyore, Hunza, and Nagar to measure species density and evaluate community dependence on these essential resources to measure species density and evaluate community dependence on these essential resources. Comprehensive field surveys and structured interviews were conducted in Danyore, Hunza, and Nagar to measure species density and evaluate community dependence on these essential resources. The findings show statistically significant (p < 0.05) variations in tree height and diameter among areas and an uneven distribution of Salix tetrasparma throughout the region, with Nagar showing the highest density. According to socioeconomic data, 42.2% of respondents know Salix’s medicinal advantages, while 91.1% utilize it for fuelwood. The sustainability of these species is threatened by overexploitation and habitat degradation despite their vital significance in agroforestry, land restoration, and handicraft production. The study offers important baseline data to guide conservation plans, sustainable management techniques, and governmental efforts to protect Gilgit-Baltistan’s Salix species’ ecological and economic value.